PERAN WARGA NEGARA MELALUI MEDIA SOSIAL DALAM MEMBENTUK OPINI PUBLIK - Habibi, Muhamad Khaerul; Normansyah, Asep Deni; Khoerudin, Cep Miftah (Cahaya Ilmu Bangsa, 2024)
The development of technology, especially social media, has had a significant impact on human daily life. Marshall McLuhan, in his book *Understanding Media* (1964), highlights the profound influence of technology on society. Meanwhile, the phenomenon of public opinion began to be recognized in Europe and the United States in the late 18th century, closely related to the idea of freedom of expression as a pillar of democracy. In the digital era, social media serves as a platform that influences individual attitudes and behaviors, while also becoming an important tool in political communication. However, behind its benefits, social media has also become a medium for spreading false information and hate speech, especially during political moments such as elections. Data from the Ministry of Communication and Information Technology (KOMINFO) shows a surge in hoax issues during the 2019 election, illustrating the challenges in shaping fact-based public opinion. This research aims to analyze the role of citizens through social media in shaping public opinion, as well as its positive and negative impacts. An interdisciplinary approach combining Civic Education and Political Science is expected to provide a comprehensive understanding of the dynamics of public opinion in the digital era. The focus of this study is on civic disposition, which is essential for supporting healthy and effective political participation. This research is titled